Effectiveness of SEFCC Interventions on Increasing Maternal Self-Efficacy in Preventing Child Stunting in Gorontalo City - Apriana, Rista; Ariani, Gusti Ayu Putri; Manumba, Ruliyani; Syahrir, Akifa; Adam, Lusiane (Universitas Padjadjaran, 2026)
Stunting is a health management issue for toddlers that negatively impacts the growth and cognitive development of preschool children. This study aims to analyze the effect of Family-Centered Care (SEFCC)-based Supportive Educational Intervention on stunting prevention self-efficacy in mothers with children aged 3–5 years. This study used a quasi-experimental design with a pretest-posttest with control group design. The instrument in this study was a questionnaire analyzed using a normality test and paired t-test. The number of samples in this study was 60 mothers with preschool-aged children, who were divided evenly into 30 respondents in the intervention group and 30 respondents in the control group. The results of the study in the intervention group showed a significant increase in the average (mean) score of mothers' self-efficacy, namely from 21.00 at the pre-test to 48.63 after the intervention (post-test). The bivariate Paired T-Test for the intervention group yielded a t-value of 34.78 with a significance level of p-value <0.001, indicating a very significant effect of the intervention. In contrast, in the control group, the average score increased slowly (from 17.90 to 22.10). The final comparative analysis using the Independent T-Test demonstrated a highly significant and unequal difference in self-efficacy between the two groups at the post-test stage (t-value = 26.849; p <0.001), with the intervention group having a significantly greater influence on the belief in stunting prevention. Family-Centered Care (SEFCC)-based Supportive Educational Interventions have been shown to significantly increase the implementation of self-efficacy in stunting prevention among mothers with children aged 3–5 years. Active involvement of the nuclear family has been shown to reduce maternal parenting distress and foster strong intrinsic motivation.Keywords: Family-centered care, maternal self-efficacy, supportive educational interventions, stunting prevention.